Synthesis, Characterization, and Anticancer Activity of Benzothiazole Aniline Derivatives and Their Platinum (II) Complexes as New Chemotherapy Agents - Md. Kamrul Islam; Ah-Rum Baek; Bokyung Sung; Byeong-Woo Yang; Garam Choi; Hyun-Jin Park; Yeoun-Hee Kim; Minsup Kim; Seongmin Ha; Gang-Ho Lee; Hee-Kyung Kim; Yongmin Chang (MDPI AG, 2021)
We describe the synthesis, characterization, molecular modeling, and in vitro anticancer activity of three benzothiazole aniline (BTA) ligands and their corresponding platinum (II) complexes. We designed the compounds based on the selective antitumor properties of BTA, along with three types of metallic centers, aiming to take advantage of the distinctive and synergistic activity of the complexes to develop anticancer agents. The compounds were characterized using nuclear magnetic resonance spectrometry, Fourier transform infrared spectroscopy, mass spectrometry, elemental analysis, and tested for antiproliferative activity against multiple normal and cancerous cell lines. L1, L2, and L1Pt had better cytotoxicity in the liver, breast, lung, prostate, kidney, and brain cells than clinically used cisplatin. Especially, L1 and L1Pt demonstrated selective inhibitory activities against liver cancer cells. Therefore, these compounds can be a promising alternative to the present chemotherapy drugs.